2016
DOI: 10.31235/osf.io/sg3j4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial distribution of rural dumpsites parameters in Romania

Abstract: 1. Spatial distribution of rural dumpsites parameters in Romania 2. Distribuzione spaziale dei parametri di rurali discariche in Romania 4. Abstract Poor waste management facilities led to uncontrolled waste disposal on improper sites in the proximity of human settlements particularly in rural areas. This bad practice prevailed in all rural regions until 16 July 2009 when these garbage dumps should be closed and rehabilitated according to Government Decision number 345/2005 which comply the Landfill Directive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Moreover, there is no legally binding practice of door to door collection service of waste and segregating of the waste materials at all by any official bodies in the town. It is this poor solid waste management service that resulting uncontrolled waste disposal [28].…”
Section: Existing Status and Spatial Coverage Of Waste Management Sermentioning
confidence: 99%
“…Moreover, there is no legally binding practice of door to door collection service of waste and segregating of the waste materials at all by any official bodies in the town. It is this poor solid waste management service that resulting uncontrolled waste disposal [28].…”
Section: Existing Status and Spatial Coverage Of Waste Management Sermentioning
confidence: 99%
“…Despite the fact that these sites are smaller than formal urban landills and scatered across peri-urban and rural regions, they are still a signiicant pollution source. Wild dumps must be mapped at municipal level across all regions in order to assess their environmental impact [3,4]. Monitoring of illegal dumping activities is crucial either in high-income countries afecting public lands, roadsides, or water bodies [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Mismanagement of plastic waste (MPW) refers to unsound disposal practices that could feed the plastic pollution of the natural environment such as open dumping/illegal dumping practices, littering behavior, open burning of plastics, or disposal in non-sanitary landfill sites. These bad practices in Romania are related to poor logistics, particularly in rural regions ( Mihai, 2015 ; Mihai & Ulman, 2022 ). Research studies regarding global plastic pollution levels use national data about the per-capita waste generation rates and plastic waste fraction of total municipal waste flow to determine the mismanagement of plastic waste (MPW%).…”
Section: Plastic Waste Managementmentioning
confidence: 99%
“…The closure of rural dumpsites in 2009–2010 revealed that most of the localities from extra-Carpathian regions had the largest open dumps (surface and volumes). This is explained by the lack of poor waste management facilities, particularly in rural areas combined with higher population density ( Mihai, 2015 ) while in the Carpathian regions, the dumps tended to be smaller and frequently located near freshwater bodies. In April-May 2019, a law enforcement campaign regarding illegal waste disposal practices in the proximity of water bodies was performed by the National Environmental Guard revealing 1908 dumps (C&DW, household waste, and other waste fractions) on riverbanks while the total inventory of illegal dumping sites detected in open environments in Romania reached 3,837 sites covering 1,384,980 m 2 ( National Environmental Guard (GNM), 2020 ).…”
Section: Macroplastic Pollution In Terrestrial and Aquatic Environmentsmentioning
confidence: 99%
See 1 more Smart Citation